HOW DOES TRANSFORMATIONAL LEADERSHIP BOOST OCB AMONG MILLENNIAL LECTURER? UNVEILING THE EMPOWERING ROLE OF SELF-EFFICACY - Diah Sofiah; Markus Hartono; Frikson Christian (Journal of Educational, Health and Community Psychology, 2023)
Nowadays, many lecturer positions in higher education are filled by millennials; by 2025, the number of millennial workers will reach 75%, which means three out of four workers are millennials. Millennials are also known as generation Y. Previous studies show that there are differences in the work values of millennials and previous generations, such that millennial workers may be reluctant to engage in organizational citizenship behavior (OCB). OCB refers to extra-discretionary role behaviors that enhance the organizational environment, which supports task performance. In today's complex and fast-paced organizations, extra-role behaviors have become critical to organizational success. Transformational leadership and self-efficacy have been found to be strong predictors of OCB, but the underlying mechanisms are unclear. This study aims to examine the effect of transformational leadership on the OCB of millennial lecturers, for which self-efficacy is a mediator. This research is a quantitative study, involving 357 millennial lecturers in Indonesia as research subjects. The results of this study indicate that self-efficacy partially mediates the effect of transformational leadership on the OCB of millennial lecturers. An increase in transformational leadership will increase OCB, either directly or through an increase in lecturer self-efficacy. The results of this study can be utilized by the government and university managers as review material.Keywords: OCB, Extra role behavior, Y generation, Lecturer, Higher education.